Amperometric adhesion signals of liposomes, cells and droplets - Ivošević DeNardis, Nadica (Array, 2009)
Summary: Individual soft microparticles (liposomes, living cells and organic droplets) in aqueous media are characterized by their adhesion signals using amperometry at the dropping mercury electrode. We confirmed that the general mechanism established for adhesion of hydrocarbon droplets and cells is valid as well for liposome adhesion within a wide range of surface charge densities. Incidents and shape of adhesion signals in liposome suspensions reflect liposome polydispersity, surface charge density and properties of phospholipid head group. Major distinction in adhesion behavior of liposomes when compared to organic droplets was identified as: (i) different values of critical interfacial tensions of adhesion at the positively and the negatively charged electrode, and (ii) appearance of signals revealing the specific interactions of phospholipid polar head groups with the electrode